Analisis Efektivitas Pelayanan Pendaftaran Rawat Jalan Melalui Aplikasi Sistem Berobat Jalan Online di Rumah Sakit Umum Daerah dr. Chasbullah AbdulMadjid Kota Bekasi - Irfan Choirul Fazri; Wahidin Septa Zahran (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
In handling a large number of queues and the gathering or overflowing of prospective patients at the registration counter, a breakthrough in health services is needed with the speed and response of officers to prepare patient files or data appropriately. A long waiting time resulted in a lack of treatment support facilities and delays in information, so a health service was created by using an application called the Online Outpatient Treatment System (SIBEROJOL) application. This study aimed to provide outpatient health services online. The Regional General Hospital dr. Chasbullah Abdulmadjid, Bekasi City has a web-based application called SIBEROJOL as a digital-based system that is used for services in storing data on prospective outpatient patients. The SIBEROJOL application has health services in online outpatient registration. The research method used in this research was qualitative with descriptive research type. In collecting the data, researchers employed observation, documentation, and interviews. The researchers examined the object of study and hold direct interactions with informants. The results showed the effectiveness of outpatient registration services by applying the Online Outpatient Treatment System at the Regional General Hospital (RSUD) dr. Chasbullah Abdulmadjid, Bekasi City, has not been effective because there were several obstacles. However, several efforts and solutions must be considered.